Exogenous shocks and exchange rate regimes - Chia, Wai-Mun (2013)
Using a dynamic stochastic general equilibrium (DSGE) model with nominal price rigidity and imperfect competition, we examine the impact of terms-of-trade and foreign interest rate shocks on some key macroeconomic variables for a small open economy under different exchange rate regimes. Numerical solutions from the model are found consistent with empirical panel VAR results of 33 Asian economies for the period of 1980–2009. From both the theoretical model and empirical evidence, we find that (i) output responses to terms-of-trade and foreign interest rate shocks are smoother in floats, (ii) price responses to terms-of-trade shocks are smoother in floats than in pegs, while its responses to foreign interest shocks are more volatile in floats than in pegs, and (iii) the effects of terms-of-trade and foreign interest shocks are more prolonged under floats.